Functional traits are key to understanding orchid diversity on islands - Taylor, Amanda; Keppel, Gunnar; Weigelt, Patrick; Zotz, Gerhard; Kreft, Holger (Ecography (Copenhagen), 2021)
The extraordinary diversity of orchids has captivated scientists for more than a century, yet their complex spatial patterns at large scales remain poorly resolved. On islands, orchid diversity patterns are especially puzzling. While some islands are centres of orchid diversity, orchids are underrepresented on most islands. To disentangle such complex patterns, key functional differences among orchids must be considered – a distinction seldom made in biogeographical analyses. Using a global dataset of 454 islands, we tested prominent hypotheses in island biogeography, while simultaneously making the distinction between epiphytes and two terrestrial life forms (geophytes and non‐geophytes). Orchid diversity was unevenly distributed across islands and life forms. Epiphytic orchid diversity strongly increased with temperature, illustrating the near confinement of epiphytes to the tropics. Geophytes became proportionally more important with increasing seasonality, highlighting their ability to withstand harsh climatic conditions. Epiphytes and non‐geophytes both displayed responses (e.g. negative relationship with seasonality) related to their dependence on consistently favourable conditions, possibly because of the absence of subterranean storage organs. This highlights that the factors explaining orchid diversity differ strongly with, and are related to, life form. We suggest that key functional differences within and across plant families be considered in future studies to better understand drivers of complex diversity patterns.